Analyzing the Development Cooperation between Indonesia and Denmark in Developing a Circular Economy - Singarimbun, Lukas (Journal of World Trade Studies, 2022)
Denmark and Indonesia have established development cooperation in developing circular economy which aims to resolve the climate change issue. This research will analyse the interest of both nations in forging international development cooperation and subsequently analyse the political economy aspect of the bilateral development cooperation between both nations. This research found that the bilateral development cooperation in developing circular economy in Indonesia is propelled by both domestic and international interests of both nations. Furthermore, through the institutionalist political economy perspective, the cooperation is not solely implemented through transferring the funds needed, but also by enhancing the technological aspect, public policy making, and institutionalizing the norms and values of circular economy in Indonesia’s society.